Nutritional Cues Tie Living Organisms to Their Environment and Its Sustainability - Adams, Melanie S.; Adams, Robert B.; Wessman, Carol A.; Demmig-Adams, Barbara (Frontiers in Nutrition, 2016)
We connect modern, intensive agriculture’s role in environmental degradation to its role in producing nutritionally unbalanced foods, and delineate specific approaches to reduce agriculture’s environmental impact, while producing healthful foods. We call attention to recently discovered genetic programs used by all living organisms to respond to their environment, and present a model of how these programs change body composition and function (of humans and their crop plants and livestock alike) in response to environmental cues. We propose that production of nutritionally balanced crops and livestock requires careful consideration of how these plants and animals are grown; the composition of plant food is modulated by growing conditions, body composition of livestock reflects their feed; composition and function of human body and brain are strongly affected by how food plants and animals are produced. We selected four nutritional features not only involved in (i) governing human health by modulating these genetic programs, but (ii) also affected by agricultural practices. These nutritional features are fat composition (especially saturated fat and the ratio of polyunsaturated omega-6 oils to omega-3 oils), carbohydrate composition (especially the proportion of carbohydrates with a high glycemic index, such as sugars and quick-burning starches) and the level of antioxidant micronutrients. We not only outline threats to human health presented by the current environment, but also potential gains in quality-of-life in a future environment designed to optimize human wellness using insights into the gene-programming effect of diet- and other lifestyle-related factors. These gains could extend beyond optimal human physical and mental health to gains in workforce productivity. The same changes in agricultural practices required to achieve these gains in human health are also needed to support environmental health and sustainable food production. The resulting vision of optimal human health and environmental health, supported by sustainable practices, is intended as an inspiring image of what sustainability has to offer to individuals and society. Our goal is to provide a transparent overview and illustrations intelligible not only to non-experts in each of the other respective areas involved but also to policy makers and the public.